ANALISIS PERBANDINGAN WAKTU PELAKSANAAN PEMBANGUNAN HARGA DAN ANTARA RUMAH SEDERHANA RUPAK DENGAN RUMAH SEDERHANA KONVENSIONAL TIPE 36 (Jurnal Spesialis Teknik Sipil (JSpTS), 2019)
One of the value engineering innovations in supporting a million housing program from theGovernment which is supervised by the Ministry of Public Works and Public Housing onhousing or residential assistance for low-income people, PT Duta Cipta Pakarperkasa whichis engaged in the Steel Industry has issued a simple house product Rupak using the concept ofgrowing houses with knockable walls made from Expandable Polystrane (foam foam) coatedwith steel plates. The purpose of this study was to obtain a comparison of the cost and time ofimplementation in building a simple Rupak and conventional type 36 house, namely by usinga descriptive analysis method that was processed to determine the RAB and standards used inRupak houses and conventional houses. It turned out to be the result that for a modest houseit needed Rp. 80,898,797.52 while for conventional simple houses Rp. 92,471,372.31. And interms of time a simple house needs 16 days whereas a conventional simple house needs 29days.Keywords: shapely houses, conventional simple houses, styrofoam, knock down walls